2014
DOI: 10.1016/j.envres.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Rice methylmercury exposure and mitigation: A comprehensive review

Abstract: Rice cultivation practices from field preparation to post-harvest transform rice paddies into hot spots for microbial mercury methylation, converting less-toxic inorganic mercury to more-toxic methylmercury, which is likely translocated to rice grain. This review includes 51 studies reporting rice total mercury and/or methylmercury concentrations, based on rice cultivated or purchased in 15 countries. Not surprisingly, both rice total mercury and methylmercury levels were significantly higher in polluted sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(164 citation statements)
references
References 187 publications
(219 reference statements)
10
151
2
Order By: Relevance
“…The obtained values exceed the Chinese National Standard Agency permissible limit (20 ng g -1 ) (CNSA, 1994), indicating the impact of mining and smelting activity in the study area. A large Hg species distribution ( Figure 2a, Table S4) variation is also observed in rice seeds from this Chinese region, as previously reported in the literature (Horvat et al, 2003;Qiu et al, 2008;Rothenberg et al, 2014;Zhang et al, 2010). The percentage of MeHg (%MeHg) fluctuates between 6 and 97% ( Figure 2a, Table S4) and it is not related to the THg concentration in rice seeds (p>0.05).…”
Section: Hg Concentration and Species Distribution In Rice Seedssupporting
confidence: 63%
See 1 more Smart Citation
“…The obtained values exceed the Chinese National Standard Agency permissible limit (20 ng g -1 ) (CNSA, 1994), indicating the impact of mining and smelting activity in the study area. A large Hg species distribution ( Figure 2a, Table S4) variation is also observed in rice seeds from this Chinese region, as previously reported in the literature (Horvat et al, 2003;Qiu et al, 2008;Rothenberg et al, 2014;Zhang et al, 2010). The percentage of MeHg (%MeHg) fluctuates between 6 and 97% ( Figure 2a, Table S4) and it is not related to the THg concentration in rice seeds (p>0.05).…”
Section: Hg Concentration and Species Distribution In Rice Seedssupporting
confidence: 63%
“…However the trend observed in rice seeds revealed that Hg is enriched in heavier isotopes for higher content of MeHg (> 50%). Such isotopic pattern (d 202 Hg) could be attributed to the divergent uptake and distribution between iHg and MeHg, since a clear dissimilar bioaccumulation factor is observed for these species (Rothenberg et al, 2011(Rothenberg et al, , 2014Zhang et al, 2010) being 800 fold higher for MeHg than for iHg (Rothenberg et al, 2014;Zhang et al, 2010). However, further studies are required to establish an unambiguous link between Hg processes and the resulting isotopic signature.…”
Section: Combination Of Speciation and Hg Isotopic Pattern For The Inmentioning
confidence: 99%
“…Especially rich in HgS deposits is the southwestern region and the Guizhou Province of China (Qiu et al, 2012a,b). Accumulation of Hg in the form of inorganic Hg and methylmercury (MeHg) by vegetables and rice from soils enriched/polluted with Hg areas of natural enrichment in region of the Guizhou Province have been documented (Li et al, 2015;Rothenberg et al, 2014;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The majority of recent studies on methylation in rice paddies have examined contaminated systems (Rothenberg et al 2014), which are beyond the scope of this paper. However, methylation has been found to occur in non-contaminated rice cultivation sites around the world including Brazil (da Silva et al 2010;Batista et al 2012;Silva et al 2012), China (Rothenberg et al 2011), and Spain (da Silva et al 2013).…”
Section: Inundated Environmentsmentioning
confidence: 99%